Analisa Persimpangan Jalan Tanpa Sinyal (Studi Kasus Simpang Tiga Jalan Sematang Borang - Jalan Siaran Kota Palembang) - Eko Nurrahman; Pujiono Pujiono; Robi Sahbar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Roads are a crucial element in land transportation infrastructure that require special management, particularly at intersections between two or more road sections. Urban development in Palembang City has led to a significant increase in population mobility and vehicle volume, particularly in areas with growing residential and commercial activity. This issue is crucial for further study, given their function as connecting routes between densely populated residential areas and community activity centers. Considering these conditions, the author was motivated to conduct a study entitled